Potentiometric Study of Phenytoin – PVC Membrane Electrodes for Determination of Phenytoin in pharmaceutical preparations - Al-Bayati, Yehya K; Karabat, Raad R (Al-Nahrain Journal of Science, 2018)
Ion selective electrodes for phenytoin were prepared using sodium tetraphenyl borate (NaTPB) ionophore and various plasticizers: di-n-butylphthalate (DBPH), tri-n-butylphosphate(TBP), o-nitrophenyloctyl ether (ONPOE) and di-octylphenylphosphonate (DOPH). The response characteristics of these electrodes, including slope of the calibration plot, the corresponding concentration range, detection limit, response time, life time, pH effect, and selectivity were studied. The experimental results showed that the best electrode was based on DOPH and DBPH as plasticizers, displaying a linear range from1.00×10−1 M to 1.00 × 10−5 M and 1.00×10−1 M to 2.00×10−5 with a Nernstian slope of 26.6 mV/decade and 26.2 mV/decade, correlation coefficient of 0.9993 and 0.9989, The detection limit was 6.00×10−6 M and 9.00×10−6, the lifetime was around 30 and 28 days respectively. The proposed electrodes were successfully applied to the determination of phenytoin in a pharmaceutical preparation.